Collaborative care for depression and anxiety disorders: results and lessons learned from the Danish cluster-randomized Collabri trials - Nadja Kehler Curth; Ursula Ødum Brinck-Claussen; Carsten Hjorthøj; Annette Sofie Davidsen; John Hagel Mikkelsen; Marianne Engelbrecht Lau; Merete Lundsteen; Claudio Csillag; Kaj Sparle Christensen; Marie Jakobsen; Anders Bo Bojesen; Merete Nordentoft; et al. (BMC Family Practice, 2020)
Abstract Background Meta-analyses suggest that collaborative care (CC) improves symptoms of depression and anxiety. In CC, a care manager collaborates with a general practitioner (GP) to provide evidence-based care. Most CC research is from the US, focusing on depression. As research results may not transfer to other settings, we developed and tested a Danish CC-model (the Collabri-model) for depression, panic disorder, generalized anxiety disorder, and social anxiety disorder in general practice. Methods Four cluster-randomized superiority trials evaluated the effects of CC. The overall aim was to explore if CC significantly improved depression and anxiety symptoms compared to treatment-as-usual at 6-months’ follow-up. The Collabri-model was founded on a multi-professional collaboration between a team of mental-health specialists (psychiatrists and care managers) and GPs. In collaboration with GPs, care managers provided treatment according to a structured plan, including regular reassessments and follow-up. Treatment modalities (cognitive behavioral therapy, psychoeducation, and medication) were offered based on stepped care algorithms. Face-to-face meetings between GPs and care managers took place regularly, and a psychiatrist provided supervision. The control group received treatment-as-usual. Primary outcomes were symptoms of depression (BDI-II) and anxiety (BAI) at 6-months’ follow-up. The incremental cost-effectiveness ratio (ICER) was estimated based on 6-months’ follow-up. Results Despite various attempts to improve inclusion rates, the necessary number of participants was not recruited. Seven hundred thirty-one participants were included: 325 in the depression trial and 406 in the anxiety trials. The Collabri-model was implemented, demonstrating good fidelity to core model elements. In favor of CC, we found a statistically significant difference between depression scores at 6-months’ follow-up in the depression trial. The difference was not significant at 15-months’ follow-up. The anxiety trials were pooled for data analysis due to inadequate sample sizes. At 6- and 15-months’ follow-up, there was a difference in anxiety symptoms favoring CC. These differences were not statistically significant. The ICER was 58,280 Euro per QALY. Conclusions At 6 months, a significant difference between groups was found in the depression trial, but not in the pooled anxiety trial. However, these results should be cautiously interpreted as there is a risk of selection bias and lacking statistical power. Trial registration ClinicalTrials.gov, ID: NCT02678624 and NCT02678845 . Retrospectively registered on 7 February 2016.